Growth of Carbon Materials on Gold Substrate by Plasma Enhanced CVD - Sperka, Jirí; Zajícková, Lenka; Jasek, Ondrej; Pamreddy, Annapurna; Havel, Josef; Schäfer, Jan; Foest, Rüdiger (International Conference on Plasma Surface Engineering, 2013)
Carbon is a versatile building element of many interesting materials that have already find practical applications in the form of thin films (diamond, DLC) or potential applications in the form of nanostructures (fullerenes, carbon nanotubes, graphene). For electronics or sensors, it is important to provide a very good contact to the functional structures. Gold is the best choice taking into account its inertness, i. e. oxidation resistance. From this point of view the investigation of the growth of carbon materials on gold is important. The carbon-gold interaction plays an important role in different fields of electronics such as atomic force microscope lithography, bioelectronics or semiconductor industry. Research in this field is developing rapidly e. g. the modification of interface structure and contact resistance between a CNT and gold electrode was recently modified by Joule melting and amorphous C-Au nanocomposite thin films were deposited by dc magnetron co-sputtering. Herein we report on the preparation and characterization of the carbon nanocomposites which were synthesized on gold substrate from methane precursor using low pressure thermal chemical vapor deposition technique and two different plasma-enhanced chemical vapor deposition (PECVD) methods. The former one PECVD proceeded in microwave reactor at low pressure and the latter one was carried out using non-thermal atmospheric pressure plasma jet (ntAPPJ). Presented approach is based on the deposition of carbon material on gold instead of the deposition of gold on carbon material which is more common. Surprisingly, we didnt find similar studies dealing with the synthesis of carbon nanocomposites using direct deposition from hydrocarbon precursor on the gold thin _lm. The surface morphology was studied by high resolution scanning electron microscopy (HRSEM). Depth-structure profile including the film thickness was observed using the focused ion beam ablation. Energy-dispersive X-ray spectroscopy (EDX), infrared reflection absorption spectroscopy (IRRAS) and laser desorption-ionization time of flight mass spectrometry (LDI-TOF MS) were used to study the chemical properties. Gold and carbon related clusters were observed by means of mass spectrometric study.